A new sector of Via XVII Necropolis in Bracara Augusta: the High Empire phase - Braga, Cristina Maria Vilas Boas (2014)
Between 2008 and 2009 a preventive excavation supervised by the Unit of Archaeology of the University of Minho was conducted in an area with approximately 5000 square meters allowing the identification of a wide sector of the Via XVII necropolis, which is one of the five roman necropolises known to have existed in Bracara Augusta. The findings enabled us to define a typological framework related with incinerations, to understand the internal organization of the necropolis and recover the ritual marks of the funerary practices between the first century BC and the second century AD.